2010
DOI: 10.2337/db09-1057
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Reactive Oxygen Species by Lovastatin Downregulates Vascular Endothelial Growth Factor Expression and Ameliorates Blood-Retinal Barrier Breakdown in db/db Mice

Abstract: OBJECTIVEOxidative stress is a key pathogenic factor in diabetic retinopathy. We previously showed that lovastatin mitigates blood-retinal barrier (BRB) breakdown in db/db mice. The purpose of this study is to determine the mechanisms underlying the salutary effects of lovastatin in diabetic retinopathy.RESEARCH DESIGN AND METHODSExpression of NADPH oxidase (Nox) 4, vascular endothelial growth factor (VEGF), and hypoxia-inducible factor (HIF)-1α; production of reactive oxygen species (ROS); and retinal vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
199
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(215 citation statements)
references
References 47 publications
13
199
0
3
Order By: Relevance
“…Importantly, this is likely to be Nox4 dependent because downregulation of Nox4 in human podocytes was also associated with attenuation of VEGF expression. Consistent with our findings, other researchers reported a link between VEGF with Nox4 in the retina, where Nox4 was associated with vascular permeability, 39 as well as similar findings in a stroke model. 40 Diabetic nephropathy is considered to be at least in part an inflammatory disorder in which progressive glomerular injury is associated with macrophage infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, this is likely to be Nox4 dependent because downregulation of Nox4 in human podocytes was also associated with attenuation of VEGF expression. Consistent with our findings, other researchers reported a link between VEGF with Nox4 in the retina, where Nox4 was associated with vascular permeability, 39 as well as similar findings in a stroke model. 40 Diabetic nephropathy is considered to be at least in part an inflammatory disorder in which progressive glomerular injury is associated with macrophage infiltration.…”
Section: Discussionsupporting
confidence: 93%
“…Accumulating reports clearly showed that bevacizumab, administered by intraocular injection, has a global effect in normalizing the pathologic intraocular environment and changing the immature, fenestrated vessels toward a normalized status by neutralizing VEGF in ocular disease (45,47). Coincidentally, as equally possessed with antagonistic action against VEGF, high-dose statins have been widely used in treating DR and complications both in clinical settings and experimental models, in consideration of its activities in decreasing retinal neovascularization, retaining endothelial barrier integrity and eventually reducing the area of hypoxia (13,48). Thus, it is reasonable to infer that the beneficial effects of high-dose simvastatin are also applicable to neovessels of tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, tumor tissues of interest were freshly dissected in 1X PBS and then 60-80 µm thick frozen tumor sections were prepared for incubation with the freshly prepared H 2 DCFDA (10 µM) for 15 min in dark at room temperature. After three washes with PBS, sections were immediately monitored by a confocal microscope and the fluorescent intensity of DCF was semiquantified using Image-Pro Plus 6.0 software (13). To determined alterations after ROS clearance, tumor-bearing mice received an intraperitoneal injection of DPI (a NADPH oxidase inhibitor) or same amount of vehicle for 5 days.…”
Section: Measurement Of Ec Permeabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The citation "Wang et al (2010)" has been changed to " Wang et al (2010)" to match the author name/date in the reference list. Please check here and in subsequent occurrences, and correct if necessary.…”
Section: Location In Chaptermentioning
confidence: 99%